Investigating the Formation Mechanism of Arene Ruthenium Metallacycles by NMR Spectroscopy. Issue 33 (November 2014) - Garci, Amine; Gupta, Gajendra; Dalvit, Claudio; Therrien, Bruno
Abstract: Invited for the cover of this issue is Bruno Therrien from the University of Neuchatel, Switzerland. The cover image uses the analogy of growing a plant in a pot to show the simple mixing of different building blocks in an appropriate solvent, followed by a germination period, before harvesting the resulting metalla‐assembly. Studying this "germination period" by NMR spectroscopy has thrown light on the formation mechanism, providing insight for the design of new arene ruthenium metalla‐assemblies. Abstract : These intelligent metalla‐cages will allow perfect control over the spatial and temporal release of the guest molecule... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 5651 ff .